The theatre of Eugene O'Neill : American modernism on the world stage - Eisen, Kurt (Critical companions (London, England), 2017)
"The Theatre of Eugene O'Neill offers a new comprehensive overview of O'Neill's career and plays in the context of the American theatre. Organised thematically, it considers his Modernist intervention in the theatre, offers readers detailed analysis of the plays, and assesses the recent resurgence in his reputation and new approaches to staging his work. It includes a study of all his major plays - The Emperor Jones, The Hairy Ape, The Iceman Cometh, Long Day's Journey into Night, A Moon for the Misbegotten and Desire Under the Elms - besides numerous other full length and one act dramas. Eugene O'Neill is generally credited with inventing modern American drama, in a time of cultural ferment and lively artistic and intellectual change. Yet O'Neill's theatrical instincts were always shaped by American stage traditions that were inextricable from his sense of himself and his own national culture. This study shows that his theatrical modernism represents not so much a break from these traditions as a reinvention of their scope and significance in the context of international stage modernism, offering an image of national culture and character that opens new possibilities for the stage while remaining rooted in its past."--Provided by publisher